Smart-city development paths: Insights from the first two decades of research. - Mora, Luca; Deakin, Mark; Reid, Alasdair (Springer, 2018)
More than 20 years have now passed since the concept of smart city first appeared in a scholarly publication, marking the beginning of a new era in urban innovation. Since then, the literature discussing this new concept and the urban-innovation approach with its orientation on information and communications technology it stands for has been growing steadily, along with the number of initiatives that cities all over the world have launched to pursue their ambition of becoming smart. However, current research still falls short of providing a clear understanding of smart cities and the scientific knowledge policy makers and practitioners both need to deal with their progressive development. In response to this shortfall, this paper offers a bibliometric study of the first two decades of smart-city research, whereby citation link-based clustering and text-based analysis are combined to: (1) build and visualize the network of scholarly publications shaping the intellectual structure of the smart city research field; (2) identify the clusters of thematically related publications; and (3) reveal the emerging development paths of smart cities that these clusters support and the strategic principles they embody. This study uncovers five main development paths: the experimental path; the ubiquitous path; the corporate path; the European path; and the holistic path. Overall, this analysis offers a comprehensive and systematic view of how a smart city can be understood theoretically and as a scientific object of knowledge able to inform policy-making processes.
Keywords: Smart City; Forschungsgeschichte; Literaturauswertung; Statistische Auswertung